Rediseño del sistema de bombeo para el mejoramiento del uso eficiente de agua y energía de la Universidad Antonio Nariño sede Santa Marta (2020)
The research is directed around the redesign and improvement of the efficiency of the pumping system of the Antonio Nariño university, due to the fact that the university demands a high consumption in the pump room, when the irrigation activity is carried out in the institution and it is It is reflected in the billing of the energy provider. Given that the university does not have an independent irrigation system that provides greater efficiency in the pumping process and in turn a use of water in the different activities that the precious liquid is used in educational purposes. The university does not see the taking of supervised measurements for the consumption of the pumps, nor is a basic maintenance plan for the pumping system taken into account, for this reason measurements were made to analyze the behavior of the pumps and provide the recommendations on how to improve your energy efficiency, in addition to lowering high energy consumption. This was achieved through the use of tools such as energy meters and soft starters, which avoid large current peaks at the moment of breaking the inertia of the motor, the improvement of the water pipes was also taken into account to avoid high pressures and water hammer that increase the consumption of the aforementioned system. Methodologically, a descriptive, quantitative and field research was used where information was obtained through bibliographic documents on the phenomenon under study